Multifunctional electrochemical application of a novel 3D AgInS2/rGO nanohybrid for electrochemical detection and HER. Issue 11 (10th September 2019) - Li, Xueqin; Shi, Yangming; Chen, Pinghua; Bai, Yingchen; Li, Guifang; Shu, Hongying; Chen, Dezhi; Li, Songjun; Jiang, Hualin
Abstract: BACKGROUND: Environmental pollution and energy depletion are two serious problems that face mankind at present, so it is urgent to develop effective methods to deal with them. Electrochemistry offers a promising solution method owing to its fast, sensitive and clean properties. Since electrode materials are significantly important to improve electrochemical performance, studies of effective electrode materials have attracted increasing interest and become a research hotspot in recent years. RESULTS: In this study, a novel multitasking electrode material 3D AgInS2 /rGO was successfully prepared, the first to couple two important electrochemical functions of sensing and hydrogen evolution reaction (HER) into one electrode material. It can highly sensitively detect 4‐nitrophenol in real water over a wide concentration range with significantly low limit of detection, outstanding stability and anti‐interference ability. Furthermore, it can effectively electrolyze water to produce H2 by HER with low onset potential, low overpotential, small Tafel slope, good durability and high stability. CONCLUSION: The study indicates that the highly conductive 3D rGO scaffold decorated with nano AgInS2 particles forms a nanohybrid, which produces positive synergistic effects to improve the electrochemical properties. This 3D AgInS2 /rGO nanocomposite is considered to have high potential to deal with environmental problems owing to its high performance in the two important functions of contaminant sensing and HER. © 2019 Society of Chemical Industry